2015
DOI: 10.7314/apjcp.2015.16.4.1409
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Trend of Cancers in the Province of Kerman: Southeast of Iran

Abstract: Background: According to increase in elderly populations, and change in lifestyle and cancer-causing behavior, the global burden of cancer is increasing. For prevention and control of disease, knowledge of population statistics of cancers and their trends is essential. This study aimed to investigate the epidemiology and trends of cancer in the province of Kerman: southeast of Iran. Materials and Methods: This analytical and cross-sectional study was carried out based on cancer registry data at the Disease Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
63
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 7 publications
1
63
0
1
Order By: Relevance
“…In Iran, BC with the frequency of 23% of women cancers is the most common form of cancer of this sex and overall, 0.9 percent of all deaths in age category of 15-49 years and 0.9 percent of all deaths in age group of 50-69 years in the country are due to BC in 2009 (Khosravi et al, 2013;Keyghobadi et al, 2015). Looking at the peak age of this cancer in Iranian women which is reported in fourth and fifth life decades reveals that it is lower than the global statistic as much as a decade (Health).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Iran, BC with the frequency of 23% of women cancers is the most common form of cancer of this sex and overall, 0.9 percent of all deaths in age category of 15-49 years and 0.9 percent of all deaths in age group of 50-69 years in the country are due to BC in 2009 (Khosravi et al, 2013;Keyghobadi et al, 2015). Looking at the peak age of this cancer in Iranian women which is reported in fourth and fifth life decades reveals that it is lower than the global statistic as much as a decade (Health).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, cancer is a major health problem in many countries (Keyghobadi et al, 2015;Razi et al, 2015;Zahedi et al, 2015;Zeinalzadeh et al, 2015). Currently cancer is the second leading cause of death in economically developed countries and the third leading cause of death in developing countries (Garcia et al, 2007;Almasi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have confirmed changes in the Epidemiology and morphology trends of the cancers in some countries and Iran (Keyghobadi et al, 2014;Razi et al, 2014;Almasi et al, 2015;Mirzaei et al, 2015;Rafiemanesh et al, 2015). Considering different incidence rate around the world, so performed studies abroad the country cannot determine the cancer situation in Iran and also there has not been yet any study about epidemiology, morphology and trend of this important disease during recent years in Iran and on the other hand, epidemiological studies are necessary for successful planning, therefore this study was done to evaluate epidemiology and morphology of blood cancer during 2003-2008. …”
Section: Introductionmentioning
confidence: 89%
“…Iran is a developing country experiencing dramatic increase in population growth especially after 1979 1 revolution while the life style of the population become progressively worse which leads 98-100 per 100,000 new cases of cancer in Iran (Mousavi et al, 2009;Keyghobadi et al, 2015;Veisy et al, 2015). Although all type of cancers are noteworthy for health systems, some type of cancers like breast, Ovary, cervix, prostate, and bladder are socially and economically dominant.…”
Section: Introductionmentioning
confidence: 99%